Unraveling IFN-I response dynamics and TNF crosstalk in the pathophysiology of systemic lupus erythematosus - Van Eyndhoven, Laura C.; Chouri, Eleni; Matos, Catarina I.; Pandit, Aridaman; Radstake, Timothy R. D. J.; Broen, Jasper C. A.; Singh, Abhyudai; Tel, Jurjen (Frontiers in Immunology, 2024)
The innate immune system serves the crucial first line of defense against a wide variety of potential threats, during which the production of pro-inflammatory cytokines IFN-I and TNFα are key. This astonishing power to fight invaders, however, comes at the cost of risking IFN-I-related pathologies, such as observed during autoimmune diseases, during which IFN-I and TNFα response dynamics are dysregulated. Therefore, these response dynamics must be tightly regulated, and precisely matched with the potential threat. This regulation is currently far from understood. Using droplet-based microfluidics and ODE modeling, we studied the fundamentals of single-cell decision-making upon TLR signaling in human primary immune cells (n = 23). Using biologicals used for treating autoimmune diseases [i.e., anti-TNFα, and JAK inhibitors], we unraveled the crosstalk between IFN-I and TNFα signaling dynamics. Finally, we studied primary immune cells isolated from SLE patients (n = 8) to provide insights into SLE pathophysiology. IFN-I and TNFα response dynamics display remarkable differences reflected by aberrant single-cell decision-making in SLE patients, uncovering a potent, yet dysregulated crosstalk between IFN-I and TNFα responses. We provide a solid dropletbased microfluidic platform to study inherent immune secretory behaviors, substantiated by ODE modeling, which can challenge the conceptualization within and between different immune signaling systems. These insights will build towards an improved fundamental understanding on single-cell decision-making in health and disease.